1996
DOI: 10.1111/j.1600-0404.1996.tb07046.x
|View full text |Cite
|
Sign up to set email alerts
|

L-arginine/nitric oxide pathway activation in platelets of migraine patients with and without aura

Abstract: Nitric oxide (NO) in platelets has been proposed as a promising tool for studying NO variations in migraine. In the present research the platelet response to collagen and the basal and collagen-induced production of NO and cGMP in platelet cytosol were assessed in migraine patients (25 with aura and 35 without aura) both interictally and ictally, and compared with the same parameters in 30 age-matched control subjects. A reduced responsiveness to collagen was found in migraine patients, particularly those with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 43 publications
2
28
0
Order By: Relevance
“…Gallai et al found that during attacks, higher NO 2 -and NO 3 -concentrations in platelets were seen in those with migraines as compared to the interictal period. 19 A recent study supported this finding and reported higher NO metabolite levels in platelets during migraine headaches, but not in the headache-free periods. 20 Nattero et al demonstrated higher serum NO levels during the migraine attack, but their patient group was very small (n = 7).…”
Section: Discussionmentioning
confidence: 68%
“…Gallai et al found that during attacks, higher NO 2 -and NO 3 -concentrations in platelets were seen in those with migraines as compared to the interictal period. 19 A recent study supported this finding and reported higher NO metabolite levels in platelets during migraine headaches, but not in the headache-free periods. 20 Nattero et al demonstrated higher serum NO levels during the migraine attack, but their patient group was very small (n = 7).…”
Section: Discussionmentioning
confidence: 68%
“…Our group found an increase in platelet NOS activity, both basal and collagen-stimulated, in migraine patients assessed between attacks [30]. This was accompanied by a significant rise in the intracellular messenger cyclic guanosine monophosphate (cGMP) [30].…”
Section: Platelets As a Model For The Study Of No Metabolismmentioning
confidence: 99%
“…This was accompanied by a significant rise in the intracellular messenger cyclic guanosine monophosphate (cGMP) [30]. This increase may account for some alterations in platelet function observed in migraineurs, such as the increase in platelet content of L-arginine and the reduced responsiveness to collagen; the latter finding was first shown by D'Andrea et al [5] and later confirmed by our group [4,30]. A recent study in migraine patients confirmed the activation of NOS in platelets, especially during attacks, by demonstrating increased NO end-products compared with headache-free period [31].…”
Section: Platelets As a Model For The Study Of No Metabolismmentioning
confidence: 99%
“…Based on these observations, our group investigated variations in ictal and interictal platelet NO production by measuring the steichiometric conversion of oxyhemoglobin to methemoglobin due to NOS activity and platelet cGMP production in migraine patients with and without aura, as compared to those of a group of age-matched control individuals [57]. Furthermore, the relationship between these variations and changes in platelet responsiveness to collagen, both ictally and interictally, were evaluated in the same patients.We found a reduced responsiveness to collagen in migraine patients, which was more accentuated during attacks.…”
Section: Cellular Modelsmentioning
confidence: 99%